Uncovering the architecture of production-driven introgression in Cinisara cattle breed - Viviana Floridia; Arianna Bionda; Katherine Daniela Arias; Annalisa Amato; Matteo Cortellari; Enrico D’Alessandro; Felix Goyache; Vincenzo Lopreiato; Paola Crepaldi; Luigi Liotta; Mario Barbato (BMC Genomic Data)
Abstract Background Local livestock breeds play a pivotal role in maintaining agricultural sustainability, conserving biodiversity, and preserving cultural heritage. These breeds often possess unique genetic characteristics tailored to their specific environments. The Cinisara is a dual-purpose local cattle breed of Podolian origin, primarily farmed in western Sicily, Italy. However, reports of spurious crossbreeding with cosmopolitan breeds aimed at improving the breed productivity exist. To assess the conservation status and ongoing selective pressures on this unique breed, we genotyped 71 unrelated Cinisara cattle (CIN_A) at 65k SNPs, and extended the dataset with publicly available genotype data of 30 Cinisara individuals sampled 20 years ago (CIN_B). We also included 194 individuals from seven cattle breeds, including the Podolica (POD) breed and the cosmopolitan Holstein (HOL) and Brown Swiss (BRW) breeds. We assessed the genetic diversity, population structure, and determined the extent of introgression from cosmopolitan breeds into Cinisara using local ancestry inference. Results Population structure analyses confirmed the Cinisara’s Podolian lineage and revealed significant HOL and BRW introgression. While both Cinisara populations, CIN_A and CIN_B, displayed broadly comparable genetic diversity to larger breeds, CIN_B showed reduced heterozygosity and increased inbreeding. CIN_A exhibited higher introgression, suggesting ongoing crossbreeding. Local ancestry was inferred using POD, HOL, and BRW references. CIN_A showed about 258/257 HOL/BRW introgressed SNPs, intercepting 186/131 genes and 1,584/1,772 QTLs. CIN_B had approximately 256/254 HOL/BRW introgressed SNPs, intercepting 218/184 genes and 547/437 QTLs. Predominantly, these regions overlapped with milk production QTLs, but some intercepted genes linked to unique Cinisara traits, like milk quality and climate adaptation, potentially altering breed typicality. Notably, CIN_B shows a potentially higher relative BRW contribution, while CIN_A shows a higher HOL contribution. Conclusion Our findings align with the reports of crossbreeding with cosmopolitan breeds to enhance the production performance of Cinisara, and reflect breeding choices such as a reduction in BRW crossing or a preference for HOL. This raises significant concerns regarding the preservation of local breeds, livestock biodiversity, and their cultural and economic value, and highlights the importance of developing informed breeding strategies that balance production improvements with the conservation of genetic heritage.